1988
DOI: 10.1056/nejm198802183180702
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Altered Water Metabolism in Psychotic Patients with Polydipsia and Hyponatremia

Abstract: Water intoxication is a serious problem in many patients with chronic psychiatric illness. In an effort to determine the mechanism of this disorder, we investigated the osmoregulation of water intake and antidiuretic function in psychiatric patients with polydipsia and hyponatremia and in matched controls with psychiatric illness but neither polydipsia nor hyponatremia. We found that a water load suppressed plasma osmolality and vasopressin and urine osmolality in both groups, but that urinary dilution and fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
1
6

Year Published

1991
1991
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(140 citation statements)
references
References 41 publications
9
124
1
6
Order By: Relevance
“…Hariprasad et al (1980) described Type II SIADH. Goldman et al (1988), in a well controlled study, found that psychiatric patients with polydipsia had higher levels of vasopressin at any given level of osmolality. They noted that changes in A VP secretion and action were not sufficient to explain the altered sodium levels and osmolality.…”
Section: Arginine Vasopressin or Antidiuretic Hormonementioning
confidence: 96%
“…Hariprasad et al (1980) described Type II SIADH. Goldman et al (1988), in a well controlled study, found that psychiatric patients with polydipsia had higher levels of vasopressin at any given level of osmolality. They noted that changes in A VP secretion and action were not sufficient to explain the altered sodium levels and osmolality.…”
Section: Arginine Vasopressin or Antidiuretic Hormonementioning
confidence: 96%
“…Acute psychosis itself can also cause AVP secretion, which often appears to take the form of a reset osmostat. 45 Although no single mechanism can completely explain the occurrence of hyponatremia in psychiatric patients with polydipsia, the combination of higher than normal water intake plus even modest elevations of plasma AVP levels from a variety of potential sources appears to account for a significant portion of such cases.…”
Section: Eahmentioning
confidence: 99%
“…Furthermore, polydipsic patients with and without hyponatremia display impaired HPA axis negative feedback (Goldman et al, 1993) that is consistent with hippocampal pathology (Goldman et al, 2006). In addition, hyponatremic polydipsic (but not normonatremic polydipsic) patients exhibit an unexplained increase in AVP secretion that contributes to their water retention (Goldman et al, 1988(Goldman et al, , 1996. Finally, this defect worsens with the stress of acute psychosis in the hyponatremic subset, culminating in episodes of lifethreatening water intoxication (de Leon et al, 1994;Goldman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%